BIMBINGAN KELOMPOK PRA-NIKAH BAGI MENCEGAH PERCERAIAN DI KALANGAN PASANGAN MUDA - Taufik Taufik (Pedagogi: Jurnal Ilmu Pendidikan, 2015)
The increasing divorce cases in the Court Religion lately raises concerns among the public and the government, given that the family is the first institution that became the backbone of the nation's progress. The divorce will have a negative impact on economic, social and cultural partner, especially for couples who have children will be able to have a negative impact on the development of children.Divorce cases indicate that many couples enter marriage are less equipped with adequate preparation, especially skills in dealing with turmoil and conflict in the household, as well as poor communication skills of each partner. These symptoms also showed that pre-marital counseling conducted by the prince of the couples getting married during this considered not effective in order to equip the readiness of young couples to marry. Therefore, it is necessary efforts to better prepare couples to be married with the activities of guidance and pre-marital counseling. Guidance Services Group premarital can be used as an alternative is offered for the purpose of prevention of divorce among young couples.